2021
DOI: 10.3390/polym13081230
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model Based on Physical Mechanisms for the Explanation of Drug Release: Application to Diclofenac Release from Polyurethane Films

Abstract: In this study, we present a method for prediction of the drug-release profile based on the physical mechanisms that can intervene in drug release from a drug-carrier. The application presented here incorporates the effects of drug concentration and Reynolds number defining the circulating flow in the testing vein. The experimental data used relate to the release of diclofenac from samples of non-degradable polyurethane subjected to static and continuous flow. This case includes simultaneously three mechanisms:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…As can be seen, the cooling time of the wax patterns was not affected by the different coolant flow rates while cooling water reaches turbulence fully. The Reynolds number can be calculated by the following Equation ( 2) [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the cooling time of the wax patterns was not affected by the different coolant flow rates while cooling water reaches turbulence fully. The Reynolds number can be calculated by the following Equation ( 2) [26].…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, the cooling time of the wax patterns was not affected by the different coolant flow rates while cooling water reaches turbulence fully. The Reynolds number can be calculated by the following Equation ( 2) [26]. Figure 17 shows cooling time of injection molded parts fabricated by ten sets of injection molds cooled with different compressed gas pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the flow rate of the medium leads to decreased mechanical stress for the PLGA film and significantly accelerates the burst drug release (~4-fold) from the PLGA film. Therefore, it is not only the intrinsic properties of drug-loaded polymers, but also their mechanical environment that influence the drug-release behavior of DESs [ 68 , 69 ].…”
Section: Synthetic Biodegradable Polymersmentioning
confidence: 99%
“…It is worth noting that each mechanism provides a different kinetic of the release from the stents. A study by Abbasnezhad et al [72] has showed the effect of the flow rate on the kinetic of the release by considering the associated mechanisms.…”
Section: Dynamic Conditionmentioning
confidence: 99%
“…For this purpose, a certain number of stents (usually one stent) to media are placed in the screwed-glass vials [73], tubes [74], or flasks [75], and then the test is performed at a certain agitation of the shaker. In most studies, the temperature intended for the experiment was kept constant at 37 • C by an incubator [72,76] or a water bath [73,77]. The agitation speed of shaker in studies considered in the range of 50 [78,79], 75 [80,81], 80 [75], 100 [73,76], 120 [77], 130 [82], 175 [74], 250 and 300 [83] rpm.…”
Section: Dynamic Conditionmentioning
confidence: 99%